State Authority and Legal Action: How to Prevent the State Misconduct? - Zamakhsyari, Ahmad Faris; Utama, Muhamad Adji Rahardian; Sulistyanti, Jihan Syahida; Baharudinsyah, Rasyanahla Ghaffar; Nabilla, Suci (Law Research Review Quarterly, 2020)
The ideal organization is the bureaucracy whose activities and objectives rationally think and divisions of duty and authority are clearly stated. There are some expert opinions on the notion of authority. According to Philipus M. Hadjon, in constitutional law, the Authority (Bevoegdheid) is described as the rule of law (Rechtsmacht). So in the concept of public law, authority relates to power. Ferrazi defines the authority as the right to do one or more management functions, which include arrangements (regulation and standardization), Management (Administration) and supervision (supervision) or specific affairs.